2016
DOI: 10.3389/fncel.2016.00072
|View full text |Cite
|
Sign up to set email alerts
|

Improving Interference Control in ADHD Patients with Transcranial Direct Current Stimulation (tDCS)

Abstract: The use of transcranial direct current stimulation (tDCS) in patients with attention deficit hyperactivity disorder (ADHD) has been suggested as a promising alternative to psychopharmacological treatment approaches due to its local and network effects on brain activation. In the current study, we investigated the impact of tDCS over the right inferior frontal gyrus (rIFG) on interference control in 21 male adolescents with ADHD and 21 age matched healthy controls aged 13–17 years, who underwent three separate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
110
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(121 citation statements)
references
References 69 publications
7
110
0
3
Order By: Relevance
“…Other studies showing improvement in working memory performance measured performance following stimulation [44, 89, 90]. Studies showing positive effects of tDCS in ADHD have primarily been conducted in adolescents [37, 45, 47, 91], and it is possible that adults with ADHD respond differently. Differences may also be due to differences in study design such as dosage and treatment duration, or to participant experiences of side effects during stimulation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies showing improvement in working memory performance measured performance following stimulation [44, 89, 90]. Studies showing positive effects of tDCS in ADHD have primarily been conducted in adolescents [37, 45, 47, 91], and it is possible that adults with ADHD respond differently. Differences may also be due to differences in study design such as dosage and treatment duration, or to participant experiences of side effects during stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…A single session of tDCS targeting the left DLPFC has been shown to improve memory, planning ability, inhibitory control, and neural efficiency during cognitive processing with minimal side effects [3335]. Some findings suggest that performance improvements may be related to current density; studies utilizing a 1mA dose have shown mixed results in an ADHD population [36, 37], whereas a higher dosage (i.e., 2mA compared to 1mA or sham tDCS) has been shown to improve cognitive performance in both healthy samples and neuropsychiatric populations [31, 38, 39]. Furthermore, concurrent performance of a challenging task to engage the targeted control circuits may offer synergistic effects on tDCS-induced neuroplastic changes, promoting greater functional connectivity between large-scale brain networks and improved neural efficiency resulting in improved performance on objective measures of cognitive control [4043].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…No AEs were seen in young patients, even after tDCS was applied with a higher than usual current density (0.497 mA/cm 2 ) and/or repeated over several days (Breitling et al, 2016; Mattai et al, 2011; Munz et al, 2015; Schneider and Hopp, 2011; Soff et al, 2016). tDCS was applied to some children during sleep without awakening them, and none reported AEs the following morning (Munz et al, 2015; Prehn-Kristensen et al, 2014).…”
Section: The Application Of Low Intensity Tes In Human Studies: Aementioning
confidence: 96%
“…During recent years, different brain stimulation and modulation techniques have been developed for different neuropsychiatric disorders [13][14][15]. Among the brain modulation techniques, transcranial direct current stimulation (tDCS) has shown interesting potentials as an alternative or adjunctive treatment for different psychiatric disorders including ADHD [12,[16][17][18][19][20][21][22][23]. TDCS is a noninvasive, lowcost, easy to use technique where a week direct current is delivered to the scalp through a pair of electrode, through which the flowing current changes the cortical excitability of the neurons and ultimately alters behavior [24].…”
Section: Introductionmentioning
confidence: 99%